Systematic review of integration of neonatal and child health interventions with pediatric HIV interventions - Brianna L Smith, MIA; Sara Sara Zizzo, MPH; Anouk Amzel, MD, MPH; Sarah Wiant, MPH; Molly C. Pezzulo, MPH; Sarah Konopka, MA; Rachel Golin, MD, MHS; Alexandra C. Vrazo, PhD, MPH (International Journal of Maternal and Child Health and AIDS, 2018)
Background/Objectives: In the last decade, many strategies have called for integration of HIV and child survival platforms to reduce missed opportunities and improve child health outcomes. Countries with generalized HIV epidemics have been encouraged to optimize each clinical encounter to bend the HIV epidemic curve. This systematic review looks at integrated child health services and summarizes evidence on their health outcomes, service uptake, acceptability, and identified enablers and barriers.